Politici sociale și globalizare în țările europene - Stanciu, Mariana (Calitatea Vieții, 2007)
This article is concerned with the less obvious influences of globalization on the social development and social protection. Issues about the hierarchy of globalization index, impact of the present international economic relations ethics on the socioeconomic gap between rich and poor countries, the consequences of these realities on the process of poverty alleviation, might be found in this text.